Impact from indoor air mixing on the thoron progeny concentration and attachment fraction. (July 2016) - de With, G.; de Jong, P.
Abstract: Despite the considerable amount of work in the field of indoor thoron exposure, little studies have focussed on mitigation strategies to reduce exposure to thoron and its progeny. For this reason an advanced computer model has been developed that describes the dispersion and aerosol modelling from first principal using Computational Fluid Dynamics. The purpose of this study is to investigate the mitigation effects from air mixing on the progeny concentration and attachment with aerosols. The findings clearly demonstrate a reduction in thoron progeny concentration due to air mixing. The reduction in thoron progeny is up to 60% when maximum air mixing is applied. In addition there is a reduction in the unattached fraction from 1.2% under regular conditions to 0.3% in case of maximum mixing. Highlights: Study demonstrates indoor air mixing as mitigation approach for thoron. A reduction in thoron progeny concentrations of up to 60% is found. Air mixing reduces the unattached fraction due to enhanced aerosol deposition.